Geology And Geological Models Of Nickel Laterite Deposit Gag Island, West Waigeo District, Raja Ampat Regency, West Papua Province - Agus Harjanto; Bambang Kuncoro Prasongko; Joko Santoso; Waluyo Hadi; Nur Alif Yusuf Putra karlina (Universitas Pembangunan Nasional Veteran Yogayakarta, 2022)
The location of the research is on Gag Island, West Waigeo District, Raja Ampat Regency, West Papua Province which is the area of PT. Nickel Gag. Based on the research flow chart, there are 3 main stages, namely data acquisition, data analysis, and synthesis. Physiography Gag Island is part of North Maluku (Northern Moluccas) which is included in the Raja Ampat Group. The drainage pattern found in the study area is the sub-dendritic alteration flow pattern (SDND). Geomorphology in the study area found denudational hills consisting of weak undulating hills D1, strong D2, and strongly eroded valleys D3. Lithology in the study area consists of 3 rock units, namely peridotite unit (Jp), dunite unit (Jd), and serpentinite unit (Js). The geological structure in the study area consists of the left horizontal fault of Gag 1 and 2, the right horizontal fault of Gag, paired joints, and veins. The geological model of Gag Island nickel laterite deposit consists of a bedrock model that affects the quality of nickel laterite deposits with a grade of 2-1.8% in harzburgite and dunite rocks; a slope model that affects laterite thickness with very gentle-slightly steep slopes >22 meters thick on harzburgite lithology; the geological structure model that influences the permeability of the bedrock with the presence of garnierite and chrysoprase mineralization in the fracture and help the leaching process. The exploration model is an application or application of a scientifically based geological model, besides that the exploration model is used as a command in finding exploration targets. Geological clues are used as an approach to search for nickel laterite deposits in the form of indications of flow patterns, geomorphology, lithology, geological structures, magmatogenic, and surrounding relationships.